Rivaroxaban versus high dose nadroparin for thromboprophylaxis after hip or knee arthroplasty - Heckmann, M.; Thermann, H.; Heckmann, F. (Hämostaseologie, 2015)
Deep-vein thrombosis and subsequent pulmonary embolism are major complications in total joint arthroplasty of the lower limbs. New oral anticoagulants are increasingly prescribed as thromboprophylaxis due to their simple administration and encouraging phase III marketing studies.In this observational study, we compared the efficacy and safety of rivaroxaban with nadroparin in 1302 unselected patients receiving hip or knee arthroplasty.Venous thrombembolism occurred in 3.3% (2.3%; 4.7%, 95% CI, n = 838) of patients receiving rivaroxaban and in 4.3% (2.7%; 6.7%, 95% CI, n = 464) of patients receiving nadroparin resulting in an absolute risk reduction (ARR) of 1.0% (–1.4%; 3.3%, 95% CI).With an odds ratio of 0.6 (0.4; 1.0, 95% CI), rivaroxaban was associated with a decreased perioperative drop in haemoglobin exhibiting an improved thromboprophylactic profile when compared to high dose nadroparin. Furthermore, transfusion rates were 8.8% (−2.7%; 19.9%, 95% CI) lower in patients receiving rivaroxaban. However, as previous studies have shown, low preoperative haemoglobin remains the most predictive factor for postoperative transfusions (OR: 2.4 [1.3; 4.4, 95% CI]).
Keywords: Thrombosis; nadroparin; rivaroxaban